KUALITAS PELAYANAN, HARGA DAN LOKASI TERHADAP KEPUASAN PELANGGAN PADA YAMAHA BISMA SUPRATMAN DENPASAR - Putu Diantara Yasa; Ida Ayu Agung Idawati; N. Paramananda (Warmadewa Management and Business Journal (WMBJ), 2025)
The increase in demand for motorcycle transport triggers a high level of competition among motorcycle manufacturers. The purpose of this study was to examine the effect of service quality, price, and location on customer satisfaction at Yamaha Bisma Supratman Denpasar. This study used a sample of 98 respondents with a sampling technique, namely purposive sampling. The data analysis technique in this study was multiple linear regression analysis using the SPSS program. The results showed that all independent variables, namely service quality, price, and location, had a positive and significant effect on customer satisfaction.